ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT TOLEDO TUKTUK SAMOSIR - Efendi Efendi; Marisi Butarbutar; Mangara Nababan (Sekolah Tinggi Pariwisata Mataram, 2020)
This research was conducted to see the job description and employee performance, and the influence of the work environment on employee performance at pt toledo tuktuk samosir. Methods of analysis with mixed methods (qualitative and quantitative). The results showed: good work environment and performance, and there is a positive and significant influence between the work environment on employee performance at pt toledo tuktuk samosir.